Identification of Glucose-Regulated Protein 78 (GRP78) as a Receptor in BHK-21 Cells for Duck Tembusu Virus Infection - Zhao, Dongmin; Liu, Qingtao; Han, Kaikai; Wang, Huili; Yang, Jing; Bi, Keran; Liu, Yuzhuo; Liu, Na; Tian, Yujie; Li, Yin (Frontiers in Microbiology, 2018)
Since 2010, outbreak and spread of tembusu virus (TMUV) caused huge losses to the breeding industry of waterfowl in several provinces of China. In this study, we identify the glucose regulated protein 78 (GRP78) as a receptor in BHK-21 cells for duck tembusu virus infection. Using cell membrane from BHK-21 cells, a TMUV-binding protein of approximately 70 kDa was observed by viral overlay protein binding assay (VOPBA). LC-MS/MS analysis and co-immunoprecipitation identified GRP78 as a protein interacting with TMUV. Antibody against GRP78 inhibited the binding of TMUV to the cell surface of BHK-21 cells. Indirect immunofluorescence studies showed the co-localization of GRP78 with TMUV in virus-infected BHK-21 cells. We found that GRP78 over-expression increased TMUV infection, whereas GRP78 knockdown by using a specific small interfering RNA inhibited TMUV infection in BHK-21 cells. Taken togather, our results indicate that GRP78 is a novel host factor involved in TMUV entry.